Judicial Discretion and Sentencing Behavior - Freeborn, Beth
This research studies the impact of changes to federal judicial discretion on criminal sentencing outcomes. The Feeney Amendment to the 2003 PROTECT Act restricted federal judges’ ability to impose sentences outside of the U.S. Sentencing Guidelines and required appellate courts to review downward departures. Using data on all federal sentences between 1999 and 2004, we examine the effect of the Feeney Amendment on the downward departures rate and prison sentence. We control for type of offense, district of sentencing, criminal history, and demographic characteristics of the offender, in order to isolate the changes in judicial sentencing due to the implementation of the Feeney Amendment. Our results suggest that the Feeney Amendment reduced the probability of a downward departure by 5% and increased prison sentences by two months. There is no evidence that judges adjust sentences in an effort to circumvent the intentions of the Feeney Amendment.Federal Sentencing Guidelines, criminal justice